strategi pengembangan destinasi super prioritas likupang minahasa utara - Dianne Olga Rondonuwu; Jongky Wuner Alfius Kamagi; Frans Victor Rattu (Faculty of Economics and Business, University of Mataram, 2024)
Likupang super priority area (DSP) is a tourism development policy mandated in the National Tourism Development Master Plan (Ripparnas) 2010-2025. Various problems encountered in the development of Likupang DSP include: tourism has not provided a significant economic impact on the community, government limitations in building infrastructure and basic tourism support, low human resources to meet international standard service quality, suboptimal management of tourist destinations, the absence of a joint forum consisting of stakeholders initiated by the government in addressing issues faced in the development and management of Likupang tourism destinations. The sample of this study consisted of 5 people from the tourism and travel industry, academics, the provincial tourism office, and tourism observers. By using SWOT analysis, it was obtained: SO strategy is a strategy to use strengths to take advantage of opportunities, consisting of: development of tourist destinations and attractions, utilizing tourist visits from cruise ships, and promoting marine tourism to China. WO strategy is a strategy to improve weaknesses after seeing existing opportunities, consisting of training, development, and community empowerment through technical guidance and certification. promotion through overseas tourism events, addition of tourism amenities such as restaurants, souvenir shops, and other public facilities. ST strategy is a strategy of using strength to anticipate threats, consisting of comprehensive promotion by all stakeholders related to DSP Likupang, partnership development through the establishment of a forum of all stakeholders, management, and development of environmentally based tourism. And the WT strategy is a strategy to anticipate threats by fixing weaknesses, namely training on the environment and waste management.